The relationship between personality traits and individual factors with perinatal depressive symptoms: a cross-sectional study - Riccardo Serra; Nicoletta Giacchetti; Francesco Saverio Bersani; Gaia Cappannini; Melania Martucci; Matteo Panfili; Carla Sogos; Franca Aceti (BMC, 2023)
Abstract Background Pregnancy is a crucial transition moment exposing women to potential mental health problems, especially depressive disturbances. Sociodemographic, pregnancy-related, and psychological factors have been related to depressive symptoms in the perinatal period. This study aims at (1) exploring personality and individual factors related with perinatal depressive symptoms, and (2) testing the mediating role of personality in the relation between characteristics of the woman's family of origin and depressive symptoms. Methods Women in the perinatal period admitted to the gynecology unit for motherhood-related routine assessments (n = 241) were included in the study. A survey on individual sociodemographic, clinical, and pregnancy-related factors was administered, also including the Edinburgh Postnatal Depression Scale (EPDS) and the BIG-5 personality test. Results Couple conflict and neuroticism were independent and directly correlated with EPDS total score (respectively: B = 2.337; p = .017; B = 0.303; p < .001). Neuroticism was a significant mediator of the relation between the presence of a psychiatric disorder diagnosis in participant's parents and the EPDS total score (indirect b = 0.969; BCCI95%=0.366-1.607). Conclusions Couple relation and neuroticism traits are individual factors related to depressive symptoms in the perinatal period. The family of origin also plays an indirect role on perinatal depressive symptoms. Screening of these factors could lead to early recognition and more tailored treatments, ultimately leading to better outcome for the entire family.